PENGARUH BRAND AMBASSADOR DAN TAGLINE TERHADAP KEPUTUSAN PEMBELIAN ONLINE DENGAN MEDIASI BRAND AWARENESS - Osak, Derby Juliana; Pasharibu, Yusepaldo (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.04.TAHUN 2020DO - 10.24843/EEB.2020.v09.i04.p04, 2020)
In today's digital era the Internet is important to make it easy for every individual who wants to shop easily and quickly. The emergence of e-commerce makes it easier for those who want to carry out online trading transactions, so e-commerce companies must introduce their mobile e-commerce to the public. This study aims to determine the effect of brand ambassadors, taglines on brand awareness and their impact on purchasing decisions on Shopee e-commerce. The sample in this study was the community in Ambarawa District, Semarang Regency. Data collection using questionnaires both offline and online were distributed to 170 respondents. The analytical method used to process data using path analysis and continued testing indirectly uses the Sobel test. The results of this study stated that the brand ambassador and tagline have a positive and significant effect on purchasing decisions. However, brand ambassador and tagline has no significant effect on brand awareness. On the other side, brand awareness able to mediate the influence of brand ambassadors and tagline towards a purchase decision.